Investigation of physico-mechanical and metallurgical characteristics in a single lap joining of polybutylene terephthalate (PBT) with aluminum alloy through surface modifications - Dufera Bulto; Devendra Kumar Sinha (Journal of Engineering and Applied Science)
Abstract In this manuscript, the joining of aluminum-magnesium-silicon alloy (AA6082) with polybutylene terephthalate (PBT) has been carried out through the hot press joining method. Surface treatments of the AA6082 samples were carried out through mechanical, chemical, and plasma treatments, and with their combination. In this investigation, the joining of dissimilar materials using hot pressing technology was employed with plasma treatment of aluminum alloy surfaces and assisted with glass fiber between the two substrates to increase bonding strength. It was found that if the surface treatment was carried out individually through plasma treatment, sandblasted, grounded, and untreated, then the shearing force of product samples with a magnitude of (0.71, 1.11, 0.94, and 0.38) kN was observed, respectively. The observation revealed that the maximum shear force attained a magnitude of 2.01 kN when the surfaces were blasted and anodized aided with two plies of glass fibers. The surface morphology of the tested specimens was characterized by scanning electron microscopy. The optimum plasma parameters were determined through water contact angle measurements, and the best wettability of aluminum alloy samples was found when three different plasma parameters at (plasma power 150 W, gas exposure time 10 min, and nozzle tip distances 2 mm) using argon gas, and a 3.1° water contact angle was measured. The current study is expected to benefit the automotive and aerospace industries in applications of fabricating body parts leading to a higher strength-to-weight ratio.